Effects of the cooking modes on commonly used pesticides residue in vegetables and their chronic dietary exposure risk in South China. Issue 1 (2nd January 2020) - Zhao, Fangfang; Liu, Jingkun
ABSTRACT: Effects of cooking modes on the real intake and chronic exposure risk of pesticide residues in vegetables are usually neglected and largely unknown. Four modes of daily meal preparation; chafing dish, soup, salad and stir-frying were studied in this work to clarify their impact on the residual pesticides in foods. A detection method for 14 types of pesticide residues in different cuisines was developed. In this work, chronic exposure risks of four pesticides were analysed by probabilistic assessment based on data from public health and a pesticide residues investigation conducted. The results showed that chafing dish and soup methods greatly lowered the types, contents and exposure risks from residue pesticides. Salad preserved almost all the pesticide residues, and the risks were also relatively high in the stir-frying method. In chafing dish and soup, pesticide residues were dispersed in the media and posed quite low threats to humans. Considering the age, infants and children were at a higher risk of exposure than other populations. Reassuringly, all of the risks were at acceptable levels. This study clarified how the cooking modes affect chronic exposure risks to pesticide residues in the vegetables. The outcomes also show the effects of cooking method on healthy daily diets.